Analysis of Channel Coding Performance in OFDMTechnique for Underwater Acoustic Communication System - Alhamidi, Machmud Roby; Puja Astawa, I Gede; Santoso, Tri Budi (Politeknik Elektronika Negeri Surabaya (PENS), 2013)
One way to increase the performance of Orthogonal Frequency Division Multiplexing System (OFDM) system is by adding a channel coding (error correction code) in order to detect and correct errors that occur when sending data.At communication of acoustic underwater channel coding is required because of the characteristics of the channel bottom water is much different compared with the air channel and errors are likely to occur.In this research it was made simulation of acoustic underwater communication system with OFDM applied channel codingin which using Hamming code (7,4) and Hamming code (15,11) that is able to correct one error and detect two errors then BCH code capable to correct two errors for BCH (15,7) and correct 9 errors forBCH (127,64) and Reed Solomon code able to correct two errors for RS (15,11) and correct 8 errors for RS (31,15). Results of the study confirm the better performance when system usesOFDM with BCH Code (127.64) than other codes that are used, starting from 1 decibel (dB) to 3 dB for the performance of BER as10 -3 on Additive Gaussian White Noise (AWGN) channel while at the multipath channel, the performance of Bit Error Rate (BER) got better result on 1 dB up to 8 dB for BER performance as10 -3.Keyword: Underwater, Orthogonal Frequency Division Multiplexing (OFDM), channel coding